Birth population survey in Huai'an in 2015: perinatal-neonatal mortality and preterm birth rate in emerging regions in China. (3rd March 2020) - Wang, H.; Yue, H.; Sun, B.; Zhu, X.; Niu, H.; Qi, T.; Ding, W.; Han, L.; Zhang, M.; Tian, Z.; Guan, H.; Yang, J.; et al.
Abstract: Objective: This survey followed the birth population-based study conducted in 2010 in Huai'an, Jiangsu Province, with the aim to estimate perinatal-neonatal mortality and preterm birth rate in emerging regions with similar maternal-fetal and neonatal care conditions in China. Materials and methods: Data of total births in 2015 were prospectively collected by regional perinatal network collaboration in Huai'an, a subprovincial region with a population of 5, 644, 500 and gross domestic production of 9082 USD per capita . Results: The 59, 424 birth registries (including 59, 023 live births and 167 stillbirths) corresponded to a birth rate of 10.5‰ and a Male-to-female ratio of 113.7:100. All births there were from 85, 16, and 6 level I, II, and III hospitals, with a delivery rate of 30.4, 40.2, and 29.4%, respectively. Of all births, 14.1% had pregnancy-associated comorbidities and complications, 54.4% (32, 226/59, 190) had cesarean delivery, and multiple pregnancies and birth defects occurred in 2.1% (1, 250) and 5.5‰ (324), respectively. The mean birth weight was 3448 ± 507 g with 13.9% being macrosomia, and 2.86% (1695/59, 190) low birth weight. Preterm birth rate was 4.06% (2404/59, 190) with a mortality rate of 8.5%. There were 94.5% recorded as healthy newborns and 5.5% (3263) requiring hospitalization after birth. The perinatal and neonatal mortality rate was 5.2‰ (167 stillbirths, 139 early neonatal deaths) and 4.0‰, respectively. Compared with the 2010 survey, these data demonstrated generally improved status of perinatal-neonatal healthcare. Conclusions: The low rates of perinatal-neonatal mortality, preterm birth and preterm mortality suggest that the concept and study protocol of perinatal-neonatal healthcare in Huai'an may serve as the benchmark for estimating regional vital statistics and perinatal and neonatal outcomes.